Spectroscopic Properties of Rare Earths in Optical Materials - Liu, Guokui; Jacquier, Bernard (Springer Series in Materials Science, 2005)
Aimed at researchers and graduate students, this book provides up-to-date information for understanding electronic interactions that impact the optical properties of rare earth ions in solids. Its goal is to establish a connection between fundamental principles and the materials properties of rare-earth activated luminescent and laser optical materials. The theoretical survey and introduction to spectroscopic properties include electronic energy level structure, intensities of optical transitions, ion-phonon interactions, line broadening, and energy transfer and up-conversion. An important aspect of the book lies in its deep and detailed discussions on materials properties and the potential of new applications such as optical storage, information processing, nanophotonics, and molecular probes that have been identified in recent experimental studies. This volume will be a valuable reference book on advanced topics of rare earth spectroscopy and materials science.